Impact assessment of the organic agriculture production training program in Northern Philippines - Alsiken-Nanglegan, Marah Joy (Plant Science Today, 2023)
A study was conducted to assess the impacts of the Organic Agriculture Production (OAP) Training Program of Ifugao State University (IFSU) on beneficiaries. The Australian Centre for International Agricultural Research (ACIAR) framework for impact assessment was used in tracing the impact pathways of the program. It utilized quantitative methods of data collection. The data were analyzed using descriptive and inferential statistics and the Likert scale. Respondents were the beneficiaries of the training that served as the treatment and non-beneficiaries that served as the control. The majority of the treatment and control respondents are young adults and middle-aged, female, married, finished secondary and college, have less than five household members, and are employed. Most of the respondents in the study have organizational affiliations. The inputs to the program were from the Technical Education and Skills Development Authority (TESDA) and the IFSU. The use of these inputs produced technological and capacity building outputs. All the training respondents received their National Certificates, which means that they are all competent in the use of the OAP technologies and that they can produce new products that they can utilize for subsistence and livelihood. The evidently used adoption pathways were capacity building and communication. Respondents from the treatment group “agreed” that their participation in the training resulted in capacity building outcomes utilized at a personal and organizational level. The training program showed significant impacts on farm income, total annual income, employment, organizational affiliation and involvement, and adoption. Policy recommendations for the improvement of the program are discussed.